A Spatial Analysis of Homicide Across Brazil's Municipalities. (May 2017) - Ingram, Matthew C.; Marchesini da Costa, Marcelo
Examining homicide across Brazil's 5, 562 municipalities, we find that violence nearby has a positive effect on local violence (diffusion effect), violence exerts an unusual negative spatial effect in small clusters of communities in northeastern Brazil, and a prominent poverty-reduction program (Bolsa Família [BF]) has mixed effects. The spatial dimensions of violence complement existing non-spatial research on violence in Brazil, and the results regarding BF offer a spatial complement to research on conditional cash transfer (CCT) programs, clarifying the sources of violence in Latin America's largest country and shedding light on the content and geographic targeting of violence reduction policies.